Knowledge and attitudes of forestry students on nature and protected areas in Greece - Efthimiou, Georgios; Ntouras, Konstantinos; Panagopoulos, Thomas (Journal of Tourism, Sustainability and Well-being, 2017)
The study and academic training of citizens in issues of forest and protected areas shapes the environmentally friendly attitudes to graduates. Attitudes include public beliefs and assessments of ecosystem management activities. In education it is necessary to redefine our values ​​and ethical norms and obligations towards man and the natural environment. The field of study and gender have an impact on environmental attitudes and behaviors of students. The protected areas are subject to ample scientific research and have educational interest. The purpose of this research is to measure attitudes on Protected Areas (PA) of Forestry students in Greece. The questionnaire used as a research tool, based on the scale FVS (Forest Values ​​Scale) which is suitably adapted for PA. Based on the results of this survey it was found that the majority of the sampled students showing more biocentric attitude to Protected Areas which is largely due to the subject of their studies. With regard to gender on the positive attitude towards the environment was found to be statistically significant in favor of women. Students largely support positive environmental attitudes and found that there is a relationship between the level of knowledge about protected areas and the attitude towards the environment.